LATE POSTPARTUM COMPLICATIONS AND ITS CORREC - Хафизова Д.Б. (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract. With a decrease in mortality, however, the risk of an increase in the number of diseases after childbirth increases; the algorithm for reducing the frequency of inflammatory complications and bleeding during childbirth and the early postpartum period is well covered in the literature.